Jurnal Kepemimpinan dan Manajemen Keperawatan - Persatuan Perawat Nasional Indonesia. Jawa Tengah (Indonesian National Nurses Associaiton of Central Java, 2018)
Leadership in nursing, management of nursing services, and management of nursing care.
Keywords: Nursing services : Administration : Periodicals; Nursing services : Indonesia : Administration : Periodicals; Nursing services : Business management : Periodicals; Nursing services : Indonesia : Business management : Periodicals; Nursing services : Business management; Nursing services : Administration; Indonesia